(untitled) (Acta Scientiarum. Biological Sciences, 2012)
Natural insecticides from plant extracts represent an alternative to the highly toxic synthetic products in order to reduce environmental contamination; however some might also be toxic for non-target organisms. The present study determined the 50% lethal concentration (48h; LC50) for adults Nile tilapia (Oreochromis niloticus) exposed to the natural insecticide Fumydro®, based on the tobacco plant (Nicotiana tabacum), and evaluated its effect on hematological variables. After preliminary tests, adult specimens of O. niloticus were exposed to four Fumydro® concentrations (200, 300, 400 and 500 Î¼L L-1). The 48h; LC50 of Fumydro® was determined at 370 ± 50 Î¼L L-1. The surviving fish after exposure to Fumydro® showed an increase in the number of red blood cells, hemoglobin concentration, mean corpuscular hemoglobin and mean corpuscular hemoglobin concentration. The number of thrombocytes and leukocytes has not changed, unlike the differential leukocyte count that presented an increased percentage of neutrophils. The results indicated that the insecticide Fumydro® is highly toxic to Nile tilapia and changes in erythrocyte variables suggested the induction to hypoxemia with low effect on the immune system.